The Effect of Polymorphisms of Estrogen Receptor Î²RS1271572 to the Incidence of Epithelial Ovarian Carcinoma - Dwi S. Indrasari (Indonesian Journal of Obstetrics and Gynecology, 2012)
Objective: To determine the effect of polymorphism of estrogen receptor Î² to the risk of epithelial ovarian carcinoma at Dr. Mohammad Hoesin Hospital Palembang Methods: This population-based case control study included 40 women with epithelial ovarian carcinoma and 40 controls, from January 2010 until December 2011. Data analysis was performed by Chi Square test. Results: Distribution of estrogen receptor beta genotypes, both GT and TT (wild type-mutant and mutant), among case subjects was significantly higher than control (24 subjects {60%} vs. 5 subjects {12.5%}). The genotype effect was statistically significant for rs1271572 (OR=2.636; p=0.039) with Chi Square analysis. Whereas the allotype effect was also statistically significant (OR=1.949; p= 0.047). Conclusion: Polymorphism of estrogen receptor Î² may play a role in the risk of epithelial ovarian carcinoma at Dr. Mohammad Hoesin Hospital Palembang. [Indones J Obstet Gynecol 2012; 36-1:32-6] Keywords: epithelial ovarian carcinoma, polymorphism of estrogen receptor Î², risk factor of ovarian carcinoma